PEMETAAN RISIKO SEBAGAI DASAR UNTUK MITIGASI BENCANA TANAH LONGSOR DI DESA MUNTUK KABUPATEN BANTUL - Sri Aminatun (TEKNISIA, 2018)
Muntuk Village Dlingo District Bantul Regency is one of the villages that are vulnerable to landslides located on the topography of the ridge to the hills in the eastern region of Bantul Regency. In each rainy season some areas in the village of Muntuk landslides occurred. Based on the map of Landslides Prone Area from the Regional Disaster Management Agency, Muntuk Village is one of the villages in Bantul Regency that has steep slopes, so it has high potential for landslides, one of the ways to mitigate the landslide disaster is to assess and analyze the risk of landslide disaster in detail. This study aims to identify the homes of residents who are in landslide threat zone, be it a high threat zone or medium threat zone. The method used in this research is descriptive method with qualitative approach combined with quantitative method used to give a clear picture about the number of houses in each zonation. Sources of data used are primary and secondary data sources through interviews and documentation. The results of this study indicate that 1) the number of households in the high risk zone is 116 houses, in the hight hazard zone is 160 houses. 2) The village of Muntuk has a high threat, medium to high vulnerability, and medium capacity, which means having a medium to high risk. 3) Recommended infrastructure development for disaster mitigation.